Fabrication of a Sensitive and Stable NiO Uric Acid Biosensor Using Ag Nanowires and Reduced Graphene Oxide - Jung-Chuan Chou; Tsu-Yang Lai; Yu-Hsun Nien; Chih-Hsien Lai; Po-Yu Kuo; Si-Hong Lin; Yu-Hao Huang; Kun-Tse Lee (Energies, 2021)
How to detect uric acid is an important issue. For the purpose of preparing a potentiometric uric acid biosensor, this research used nickel oxide (NiO) as the sensing film to deposit it onto the substrate by radio frequency sputtering, then modified it with reduced graphene oxide (rGO) and silver (Ag) nanowires. Reduced graphene oxide (rGO) not only has excellent electrical conductivity, but also can make the surface of the film have a larger surface area, while AgNWs have also been proven to improve catalytic activity; hence, these two materials were chosen as sensor modifiers. Finally, the stability and the various characteristics of the uric acid biosensor were investigated using a voltage–time (V–T) system. The results showed that the AgNW–uricase/rGO/NiO uric acid biosensor has average sensitivity with 4.66 mV/(mg/L). In addition, the sensor has good stability.